Upaya Meningkatkan Minat Baca Menggunakan Metode Diskusi Pada Siswa Kelas V SDN 101776 Sampali - Mellisa Pita Butarbutar; Alfredo Batubara; Vania Rodearni Sihombing; Yusfi Laili Pasaribu; Khairunnisa Khairunnisa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The aim of this research is to describe the reading interest of fifth-grade students at SD 101776 Sampali, identify the contributing factors, and seek solutions to improve it. The subjects of this study are the fifth-grade students of SD Negeri 101776 Sampali. The research employs a descriptive qualitative method. Data collection techniques include interviews and questionnaires to ensure objective data gathering. Based on observations and interviews with the fifth-grade teacher at SD Negeri 101776 Sampali, supported by distributing questionnaires to the students, it was found that students show little enthusiasm for reading and seldom seek out answers on their own. Instead, they often ask for answers that are already available in the reading materials. Students tend to read only when instructed by the teacher. Even reading textbooks is often done only when there are exams or tests. The low interest in reading among students is also influenced by the type of reading materials available. Typically, students are required to read materials related to their school subjects and are pressured by upcoming exams. This leads to a situation where students view reading as a means to achieve grades rather than for enjoyment.